Tourism and Circular Economy: A Case Study from Kumaon Himalayas - MEHDI, Syed Asghar (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025DO - 10.14505/jemt.v16.3(79).08, 2025)
This study explores the integration of circular economy principles into the tourism sector, presenting a shift from the traditional linear model of "take, make, dispose" to a more sustainable and regenerative framework. The circular economy emphasizes reducing waste, reusing resources, and promoting sustainable consumption, making it highly relevant for tourism, a sector with high resource intensity and environmental impact. The objective of this Study is to qualitative and practical establishment of principles of tourism circularity in one of the untapped tourism zones of Uttarakhand State through Local Community Involvement. The paper outlines the theoretical foundations of circularity and applies them to tourism through strategies like resource efficiency, waste minimization, sustainable infrastructure, and local community engagement. Glancing through the case studies of current circular practices in Amsterdam and luxury resorts in the Maldives and Thailand – the design of the study establishes the community-driven initiatives in the Chhera Village of Kumaon Himalayas as the primary research of the author – demonstrating the successful positioning of local communities induced circular tourism as a practically feasible transformative approach capable of addressing the environmental and socio-economic challenges facing the global tourism industry towards strategizing for a regenerative future. The study has the limitation of reciprocating the results in the Mountain communities or more aptly the Himalayan regions. The paper is the practical attempt towards the shift from the traditional linear model to a more sustainable and regenerative framework towards the better society and environment along with sustainable tourism growth.